Young People’s Attitudes Toward the World of Work in Three Canadian Labour Markets - Taylor, Maurice C.; Boss, Marvin W.; Bédard, René; Thibault, Carol J.; Evans, Karen (Canadian Journal of Counselling and Psychotherapy, 1992)
The purpose of the study was to examine the attitudes ofyoung people soon to enter the work force in three distinct Canadian labour markets. In addition, the relationship between gender and work related opinions was also investigated. The instrument consisted of four subscales taken from a questionnaire adapted and developed in the United Kingdom 16-19 Adolescent Identity Formation Initiative and two subscales taken from the Attitude Toward the World of Work Index. The instrument was administered to 923 senior high school students in Newfoundland, Ontario, and British Columbia. Significant differences were obtained for both group and gender on the variables attitude toward training for new technology, belief in work, and job security. For self-efficacy and locus of control significant gender differences were found.